Fixed-Point Theorems for Systems of Operator Equations and Their Applications to the Fractional Differential Equations - Xinqiu Zhang; Lishan Liu; Yumei Zou (Journal of Function Spaces)
We study the existence and uniqueness of positive solution for a class of nonlinear binary operator equations systems by means of the cone theory and monotone iterative technique, under more general conditions. Also, we give the iterative sequence of the solution and the error estimation of the system. Moreover, we use this new result to study the existence and uniqueness of the solutions for fractional differential equations systems involving integral boundary value conditions in ordered Banach spaces as an application. The results obtained in this paper are more general than many previous results and complement them.